A creative and recreative conceptualization of source text : The case of journalistic translation - Huotari, Léa (John Benjamins Publishing Company, 2026)
This chapter examines the source text concept in journalistic translation, focusing on foreign news reporting. It emphasizes the characteristics of source texts in newswriting, prompting a reevaluation and expansion of the source text conceptualization within translation studies. Drawing on Jakobson’s (1959) translation typology, the article categorizes source texts by their diversity, language, and degree of mediation. A case study on the coverage of the 2022 French presidential election by the Finnish newspaper Helsingin Sanomat exemplifies this categorization. The analysis shows that foreign reporting does not rely solely on traditional interlingual source texts; it also employs intralingual and intersemiotic source texts. Furthermore, it demonstrates the dependence of newswriting on a multitude of disparate, fragmented, and multilayered source texts.
A (Re)turn to the Source Text